2001
DOI: 10.1108/13639510110390945
|View full text |Cite
|
Sign up to set email alerts
|

Community policing and socialcapital

Abstract: This paper argues for the utilization of the social capital concept in studying, evaluating, or implementing community oriented policing (COP) strategies. Social capital is helpful in measuring COP implementation effectiveness because it is central to COP issues such as trust and genuine dialogue between different groups, the ability to collectively tap into various resources, and the ability of individuals to work together to solve various problems. Findings from a study conducted in Iowa utilizing focus grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 17 publications
0
32
0
Order By: Relevance
“…The ways in which participants envisioned community relations with the MCPD was strongly in line with COP, particularly with respect to assigning officers semi-permanently to specific geographic areas, and with respect to community members having input into decision-making and policy determination (Gianakis & Davis, 1998;Maguire & Mastrofski, 2000;Pino, 2001). With the notable exception of the command officers, who viewed their jobs and the role of the MCPD as mainly reactive, police and citizens alike expressed a desire for closer ties between police and community members.…”
Section: Thematic Categoriesmentioning
confidence: 90%
“…The ways in which participants envisioned community relations with the MCPD was strongly in line with COP, particularly with respect to assigning officers semi-permanently to specific geographic areas, and with respect to community members having input into decision-making and policy determination (Gianakis & Davis, 1998;Maguire & Mastrofski, 2000;Pino, 2001). With the notable exception of the command officers, who viewed their jobs and the role of the MCPD as mainly reactive, police and citizens alike expressed a desire for closer ties between police and community members.…”
Section: Thematic Categoriesmentioning
confidence: 90%
“…Commitment at a senior level in partners and the permeation of this throughout the organisation is vital to create an endogenous culture disposed to external collaboration (Allen et al, 2001;Taylor, 2001). Further partnership building measures beyond IS provision are required, as noted by others in the context of multi-agency crime prevention (Pino, 2001;Virta, 2002). The latter author recommends, for example, a ''learning by doing'' approach to developing effective partnership.…”
Section: Ep3mentioning
confidence: 95%
“…Perceptions of police legitimacy and social cohesion appear to be highly related to assisting policing efforts; however, other factors have also been found to stimulate resident involvement. For example, in addition to actively participating in a neighborhood organization that specifically focuses on crime issues, residents who are civically engaged and actively involved in community life in general are more likely to cooperate with the police than are those residents who are less civically engaged (Duffee, 1990; Hawdon and Ryan, 2009; Pino, 2001). For example, Pino (2001) found that most of the individuals involved in police‐initiated anticrime programs were already involved in their communities prior to the implementation of the anticrime programs.…”
Section: Theoretical Backgroundmentioning
confidence: 99%